The alarming community concern on household insecticide exposure and usage - Abd Hamid, Abdul Alif; Md Isa, Muhammad Lokman; Mat Yusof, Afzan; Lee, Siew Pien; Nik Hassan, Nik Fakhuruddin; Muhammad, Hussin (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2019)
The utilization of insecticide in a household environment is a necessity especially for those living in the tropical country such as Malaysia. Tropical climate with high humidity and urbanization lead to pests breeding problem hence contributing to the spread of vector diseases such as dengue. Household insecticide such as aerosol sprays, coils and mats are made from a combination of chemicals from type 1 pyrethroid group which are recognized as safe and have minimal toxic effects on human. However, there have been cases of accidental and intentional insecticide poisoning which demonstrates the lack of studies on factors of knowledge, attitude and practice of insecticide usage, the exposure as well as clinical presentation since the symptoms are similar to other compounds which may lead to misdiagnosis. These insecticide chemicals do not only exert toxic effects to pest but to human too due to its highly toxic characteristic which causes diseases such as asthma, cancer, and other diseases following short or long-term exposure to the chemicals. As a result, there is a growing community health concern regarding the uncertainty and risk of insecticide exposure to human. Thus, the risk assessment of community’s knowledge, attitude and practice regarding the insecticide are essential in aiding towards the development of improving insecticide profile, safer insecticide handling and exploration of insecticide alternative. This will result in better insecticide awareness, as well as minimize the insecticide risk exposure and its adverse health effects to the community.